Physical activity, motor function, and white matter hyperintensity burden in healthy older adults - Fleischman, Debra A. (Neurology, 2015)
OBJECTIVE: To test the hypothesis that physical activity modifies the association between white matter hyperintensity (WMH) burden and motor function in healthy older persons without dementia. METHODS: Total daily activity (exercise and nonexercise physical activity) was measured for up to 11 days with actigraphy (Actical; Philips Respironics, Bend, OR) in 167 older adults without dementia participating in the Rush Memory and Aging Project. Eleven motor performances were summarized into a previously described global motor score. WMH volume was expressed as percent of intracranial volume. Linear regression models, adjusted for age, education, and sex, were performed with total WMH volume as the predictor and global motor score as the outcome. Terms for total daily physical activity and its interaction with WMH volume were then added to the model. RESULTS: Higher WMH burden was associated with lower motor function (p = 0.006), and total daily activity was positively associated with motor function (p = 0.002). Total daily activity modified the association between WMH and motor function (p = 0.007). WMH burden was not associated with motor function in persons with high activity (90th percentile). By contrast, higher WMH burden remained associated with lower motor function in persons with average (50th percentile; estimate = −0.304, slope = −0.133) and low (10th percentile; estimate = −1.793, slope = −0.241) activity. CONCLUSIONS: Higher levels of physical activity may reduce the effect of WMH burden on motor function in healthy older adults.